The housing of the people of Ireland during the period 1841-1901 - Matheson, Robert E. (Statistical and Social Inquiry Society of Ireland, 1906)
I purpose this evening presenting to the Society a short review of the results of the inquiries made at each successive decennial Census from 1841, into the class of Houses in Ireland, and the accommodation afforded by them, with some observations regarding the results of the special investigation into the number of Tenements of less than five rooms made in connection with the Census of 1901.
Read Friday, 5th June, 1903
Keywords: Housing, Ireland; Living standards, Ireland; Census of Ireland 1901; Tenements, Ireland; Census, Ireland; 314.15